1989
DOI: 10.1021/tx00009a011
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of eugenol by myeloperoxidase in polymorphonuclear leukocytes

Abstract: Eugenol has recently been associated with the toxic effects of clove cigarettes on human lungs. We have studied the metabolism and adverse effects of eugenol on human polymorphonuclear leukocytes (PMNs). Myeloperoxidase, isolated and purified from human PMNs, catalyzed the oxidation of eugenol to a reactive intermediate which is likely to be a quinone methide. Eosinophil peroxidase, lactoperoxidase, prostaglandin H synthase, horseradish peroxidase, and rat intestinal peroxidase also supported this hydrogen per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…For example, Thompson et al suggested that oxidation of p-eugenol by horseradish peroxidase occurs via a one-electron pathway yielding a phenoxyl radical. 14) Similar observations were made for other phenolic compounds, such as phenol, 5) BHA, 15) acetaminophen, 16) quercetin 17) and 17b -estradiol. 6) Next, we investigated how phenolic compounds affect Eq.…”
Section: Resultssupporting
confidence: 64%
“…For example, Thompson et al suggested that oxidation of p-eugenol by horseradish peroxidase occurs via a one-electron pathway yielding a phenoxyl radical. 14) Similar observations were made for other phenolic compounds, such as phenol, 5) BHA, 15) acetaminophen, 16) quercetin 17) and 17b -estradiol. 6) Next, we investigated how phenolic compounds affect Eq.…”
Section: Resultssupporting
confidence: 64%
“…The insertion of oxygen, however, is non-enzymatic and dependent on the particular structure of curcumin that enables a radical intermediate to undergo reaction with molecular oxygen and to further rearrange the peroxide into a stable product. Other natural phenolic compounds that react at the peroxidase site of the COX enzymes, for example eugenol and resveratrol, undergo a similar initial hydrogen abstraction to yield a phenoxyl radical but fail to incorporate molecular oxygen as part of the transformation since phenoxyl radicals are unreactive to O 2 (39,40). By donating a hydrogen, many flavonoids and other plant phenolic compounds have been shown to inhibit the activity of various LOX enzymes (41).…”
Section: Discussionmentioning
confidence: 99%
“…as obtained by chemical synthesis or flash photolysis of the corresponding phenols (22)(23)(24)(25)(26). However, spectra of the p-quinone methides of vanillyl alcohol and 4-(methoxymethyl)phenol have never been described.…”
Section: Discussionmentioning
confidence: 99%